2018
DOI: 10.1021/acsnano.7b08129
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient All-Solution Processed Inverted Quantum Dots Based Light Emitting Diodes

Abstract: In all-solution processed inverted quantum dots based light emitting diodes (QLEDs), the solvent erosion on the quantum dot (QD) layer prevents devices from reaching high performance. By employing an orthogonal solvent 1,4-dioxane for the hole transport layer (HTL) poly(9-vinlycarbazole) (PVK), the external quantum efficiencies (EQE) of red QLED is increased 4-fold, while the luminous efficiencies (LE) of blue QLED is enhanced by 25 times, compared to the previous devices' record. To further improve the device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 45 publications
0
96
0
Order By: Relevance
“…Inorganic metal‐oxide semiconductors possess high carrier mobility, and great chemical stability, making them better candidates for PeLEDs than their organic counterparts. Zinc oxide nanoparticle (ZnO NP) is an inorganic metal‐oxide material with better electron mobility (≈2 × 10 −3 cm 2 V −1 s −1 ) than that of TPBi (≈5 × 10 −5 cm 2 V −1 s −1 ), and is more chemically stable than TPBi, which can facilitate electron transport in the EIL and improve device stability for practical applications . Thus, ZnO NPs should work as a better EIL in PeLEDs.…”
Section: Device Performances Of Pure Fapbbr3‐based Peleds With Diffmentioning
confidence: 99%
“…Inorganic metal‐oxide semiconductors possess high carrier mobility, and great chemical stability, making them better candidates for PeLEDs than their organic counterparts. Zinc oxide nanoparticle (ZnO NP) is an inorganic metal‐oxide material with better electron mobility (≈2 × 10 −3 cm 2 V −1 s −1 ) than that of TPBi (≈5 × 10 −5 cm 2 V −1 s −1 ), and is more chemically stable than TPBi, which can facilitate electron transport in the EIL and improve device stability for practical applications . Thus, ZnO NPs should work as a better EIL in PeLEDs.…”
Section: Device Performances Of Pure Fapbbr3‐based Peleds With Diffmentioning
confidence: 99%
“…Not long ago, Liu et al reported highly efficient all-solution processed 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 inverted R/G/B QLEDs with peak EQEs of 12.7 %, 5.29 % and 5.99 %, respectively. [34] Via selecting 1,4-dioxane as an orthogonal solvent for PVK, the EML damage induced by the spin-coating of HTLs was minimized, which was verified by the identical PL intensities after the deposition of multiple HTLs, as shown in Figure 8 (c). What's more, Figure 8 (d) showed clear interfaces in the line scan analysis of elements distribution, indicating the QD layer was well protected from solvent erosion.…”
Section: All-solution-processed Inverted Qledsmentioning
confidence: 78%
“…Liu and co-workers introduced a double-layer HTL structure by combining poly(9-vinlycarbazole) (PVK) and poly [(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))-diphenylamine)] (TFB) together, and thus a stepwise energy level for hole injection is formed by this means. [34] The improved hole injection was verified by the enhanced current density of the hole-only device with double-layer HTL, which stemmed from the reduced hole injection barrier and the [36], [40] and [43]) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 high mobility of TFB (~1.0 3 10 À2 cm 2 /(V s)).…”
Section: Charge Transport Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…causes significant surface roughness in the films, which could be a serious trouble of transparent electrodes. [3][4][5] On the opposite side, the traditional solid metal electrodes like Al and Ag are still depend on deposited via vacuum thermal evaporation, which is expensive. Liquid metals based on eutectic gallium-indium (EGaIn) is a potential candidate with great radial availability.…”
Section: Introductionmentioning
confidence: 99%